Chapter 18: Handling, Cooling and Sanitation Techniques for Maintaining Postharvest Quality - Steven A. Sargent; Mark A. Ritenour; Jeffrey K. Brecht (EDIS, 2019)
This chapter focuses on methods and techniques for reducing losses in postharvest quality during typical commercial handling operations. This document is HS719, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.